PEMANFAATAN KOMPOS AMPAS TEBU PADA TANAMAN SORGUM (Shorgum bicolor (L.) Moench) DI LAHAN KERING : OPTIMALISASI PEMANFAATAN LAHAN KERING DI PROVINSI JAMBI - Soverda, Nerty; Evita, Evita (Universitas Jambi, 2022)
Sorghum is one type of cereal plant that has great potential to be developed in Indonesia because it has a wide adaptation area. Sorghum has been known and cultivated for a long time in several regions in Indonesia. The opportunity to increase production through increasing productivity is still very large because up to now the productivity that has been achieved is only 60% of the potential yield of each new variety that has a potential yield of 6 tons / ha. One of the causes of low sorghum production is due to minimum fertilization and nutrient-poor soil. Efforts that can be made to keep crop production balanced will require innovation in the supply of environmentally friendly plant nutrients, one of which is by utilizing bagasse waste into organic fertilizer. The study was conducted at the Experimental Garden of the Faculty of Agriculture, Jambi University, Mendalo Indah Village, Jambi Luar Kota District, Muaro Jambi Regency which was located at an altitude of 35 m above sea level and Ultisol soil type. The study aimed to determine the effect of bagasse compost on the growth and yield of sorghum and to obtain a dose of bagasse compost that can provide the best growth and yield of sorghum. This study was conducted using a randomized block design (RBD) with one factor, namely the dose of organic bagasse organic fertilizer consisting of 4 levels of treatment. The treatment used in this study was (P0) administration of inorganic fertilizers, (P1) administration of 5 tons / ha bagasse organic fertilizer, (P2) giving 10 tons / ha bagasse organic fertilizer, (P3) giving bagasse organic fertilizer 15 ton / ha. The variables observed were plant height, number of leaves, age of flowering, root dry weight, plant dry weight, panicle length, seed weight per plant, weight of 1000 seeds, and yield per hectare. The results showed that bagasse compost treatment had a significant effect on plant height. However, there was no significant effect on the number of leaves, age of flowering, root dry weight, dry weight of plants, panicle length, weight of 1000 seeds and dry seed weight of planting and harvest index